Effects of stocking density on finishing pig growth performance - Thomas, L. L.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Woodworth, Jason C.; Dritz, Steven S. (My University, 2016)
A total of 405 pigs (PIC 327 × 1050) from 2 consecutive finishing groups (group 1 initially 66 ± 1.8 kg BW, group 2 initially 61 ± 2.5 kg BW) were used to examine the effects of stocking density on finishing pig growth performance. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 3 treatments with either 7 or 8 replications per treatment (group 1 and 2, respectively). Pens were stocked with 9 pigs, and adjustable gates provided treatments that allowed for 0.84, 0.74, or 0.65 m2 per pig. All pigs were fed the same diets fed in 3 phases. Pigs were provided with 7.91 cm of feeder space per pig. In both studies, as stocking density decreased, ADG and ADFI increased (linear, P < 0.019), but there was no difference in G:F. As a result, final weight was 3.9 and 5.3 kg greater (linear, P ? 0.005) in groups 1 and 2, respectively, when comparing the lowest to the highest stocking density treatments. When comparing growth performance to a suggested required k-value of 0.0336, performance should have been affected above 122, 102, and 83 kg at 0.84, 0.74, and 0.65 m2 per pig. In group 1, performance should not have been affected until after 109.0 kg, 94.0 kg, and 80.3 kg for the 0.84, 0.74, and 0.65 m2 per pig treatments, respectively. However, in group 1 even after d 14 (less than 74.5 kg), negative effects of increased stocking density were observed on ADFI (linear, P < 0.08). In group 2, performance should not have been affected until after 118 kg, 87 kg, and 74 kg for the 0.84, 0.74, and 0.65 m2 per pig treatments. Similar to group 1, feed consumption and consequently ADG decreased linearly (P ? 0.033) as stocking density increased, before pigs reached the k-value that should have influenced performance. Overall, this study indicates that increasing stocking density resulted in poorer ADG driven by a reduction in ADFI and the accepted k-value of 0.0336 might underestimate the impact of increased stocking density.
Citation: Thomas, L. L., Goodband, R. D., Tokach, M. D., DeRouchey, J. M., Woodworth, J. C., & Dritz, S. S. (2016). Effects of stocking density on finishing pig growth performance. Journal of Animal Science, 94, 54-54. doi:10.2527/msasas2016-115
Keywords: Finishing Pig; Space Allowance; Stocking Density; Agriculture